Occupation and head and neck cancer: a population-based case-control study in France. (19th October 2011) - Paget-Bailly, Sophie; Carton, Matthieu; Guida, Florence; Radoï, Loredana; Cyr, Diane; Wanzy, Kamel; Schmaus, Annie; Cenée, Sylvie; Menvielle, Gwenn; Papadopoulos, Alexandra; Stücker, Isabelle; Luce, Danièle
Abstract : Objectives: To investigate the association between head and neck cancer (HNC) and occupation in men. Methods: As part of a large population based case-control study conducted in France between 2002 and 2007 (the ICARE study), 1924 incident male HNC cases and 2780 male population controls were interviewed. Detailed lifetime occupational histories, as well as information on potential confounders were collected. A preliminary analysis based on job titles was performed. Odds-ratios (OR), adjusted for age, smoking and alcohol drinking, and 95% CIs were estimated using unconditional logistic regression. Results: The risk of HNC was significantly increased for dry cleaners (OR: 6.9, 95% CI 1.5-30.9), building caretakers and cleaners (OR: 2.0, 95% CI: 1.2 to 3.2), rubber and plastics product makers (OR: 1.9, 95% CI: 1.1-3.4), metal processors (OR: 1.9, 95% CI: 1.2 to 3.0), bricklayers and other construction workers (OR:1.7 ; 95% CI :1.4 to 2.1), plumbers and welders (OR: 1.5, 95% CI: 1.2 to 2.0), food and beverages processors (OR:1.5, 95% CI:1.1-2.0), cooks and waiters (OR: 1.5, 95% CI: 1.1 to .2.1), painters (OR: 1.4, 95% CI: 1.0 to 2.1), material-handling and related equipment operators, dockers and freight handlers (OR: 1.3, 95% CI : 1.0 to 1.6), blacksmiths, toolmakers and machine-tool operators (OR: 1.3, 95% CI: 1.0 to 1.6). Teachers, managers and clerical workers had a significantly decreased risk. Conclusions: These preliminary results suggest that occupational factors may play a substantial role in the risk of HNC. Assessment of exposure to several substances is in progress, and will help identify specific causal agents.